Andy and Don [large type] : the making of a friendship and a classic American TV show - De Visé, Daniel (Center Point Large Print, 2015)
"A lively and revealing biography of Andy Griffith and Don Knotts, celebrating the powerful real-life friendship behind The Andy Griffith Show--one of America's most iconic television programs"--